Rewards dan Punishments; Indera Pendidikan Integrasi dalam Eksekusi Edukasi Kedisiplinan - Yani Pratiwi; Iqbal Mustakim; Maulidyah Safruddin; Maemonah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2023)
A technique used in the teaching and learning process, the application of reward and punishment to pupils in a preventive or repressive manner, and has a significant impact on their behavior and discipline. This study tries to describe how rewards and penalties are used to shape student discipline. A case study-style qualitative research methodology was adopted. In this study, interviews, observation, and documentation were the primary data collection methods. To determine data validity, source triangulation and technical triangulation are used. According to this study, applying rewards will lead to pupils having a disciplined attitude by communicating rewards in the form of prizes and expressing gratitude in the form of gifts. As opposed to using a piecemeal warning system, impulsive warnings, and written warning letters when applying punishment to shape a student's disciplinary attitude. Using process assessments, or evaluations that are applied when the teaching and learning process takes place, such as by observing students' behavior each day while they are in the madrasah environment, is one way to measure the use of rewards and punishments when forming students' discipline attitudes.